التحليل الاستراتيجي في المشاريع الصغيرة والمتوسطة في الجمهورية اليمنية - العطاس, وليد أحمد صالح (Recherches économiques et managériales; عدد 22 (2017): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(Décembre), 2018)
للتحليل الاستراتيجي أهمية كبرى لمختلف المؤسسات الاقتصادية، ومع اختلاف وتنوع أدواته يصعب على المؤسسات استخدام جميع هذه الأدوات . غير أن الطبيعة الخاصة لكل مؤسسة وخصوصيتها أفرزت نوع من إدراك هذه الأهمية خصوصاً لدى المؤسسات الصغيرة والمتوسطة، لذلك سأحاول من خلال هذا المقال إلقاء مساحة من الضوء على التحليل الاستراتيجي وبعض المفاهيم المرتبطة به، وما يتعلق بالمؤسسات الصغيرة والمتوسطة مع التركيز على هذا النوع من المؤسسات في الجمهورية اليمنية مستعرضا مجموعة من النقاط التي تفيد وتوضح الإشكالية الموضوعة . الكلمات المفتاحية : التحليل الاستراتيجي – أدوات التحليل الاستراتيجي – المؤسسات الصغيرة والمتوسطة في اليمن – برامج ومؤسسات تمويل المؤسسات لصغيرة والمتوسطة في اليمن Abstract Despite of the significance of the strategic analysis for the several economic institutions and its multifarious implements, it is still difficult for the institutions employing all these implements. However, the own peculiarity of each institution, especially the Small and medium-sized enterprises ones, leads to realize this significance. In this regard, the current essay sheds light on the strategic analysis, some of its related concepts, and issues that are related to the junior and intermediate institutions with a focus on such institutions in Yemen; exposing some points that aim to explain the problematic stated for the present issue. key words : Strategic Analysis - Strategic Analysis Tools - Small and Medium Enterprises in Yemen - Small and Medium Enterprise Finance Programs and Institutions in Yemen